2021
DOI: 10.3390/met11030522
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Preparation and Heat Treatment on Mechanical Behavior of Hybrid Aluminum Parts Manufactured by a Combination of Laser Powder Bed Fusion and Conventional Manufacturing Processes

Abstract: Today, in industry, laser-based additive manufacturing (LAM) is used to produce high-value parts of very complex designs that are not manufacturable by conventional technologies; this process’ low production throughput and high cost prevent it from being used more extensively. One way to exploit the benefits of LAM in industry is to have it combined with lower-cost manufacturing technologies. In a hybrid approach, LAM can be integrated within an assembly line’s welding station to complete the manufacturing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This finding suggested potentially strong default adhesion at the early bonding stage. Our findings align with and expand upon the work of Tommassi et al, 30 who explored the influence of preform surface treatments on joining properties in direct metal laser sintering, highlighting the potential significance of substrate engineering for adhesion enhancement. Similarly, Mouchard et al 31 observed, using a laser-blown powder process, that blasting surface preparation significantly impacted fabrication, influencing the single-track geometry and promoting larger, deeper welds.…”
Section: Build Plate Surfacesupporting
confidence: 89%
“…This finding suggested potentially strong default adhesion at the early bonding stage. Our findings align with and expand upon the work of Tommassi et al, 30 who explored the influence of preform surface treatments on joining properties in direct metal laser sintering, highlighting the potential significance of substrate engineering for adhesion enhancement. Similarly, Mouchard et al 31 observed, using a laser-blown powder process, that blasting surface preparation significantly impacted fabrication, influencing the single-track geometry and promoting larger, deeper welds.…”
Section: Build Plate Surfacesupporting
confidence: 89%
“…It has rich potential for many other applications, such as wearable devices with different bodily functions [6] or other biomedical applications, e.g., custom-made implantable devices. On the other hand, the factors majorly limiting the use of AM are the low production throughput and its related costs [7]. In addition, due to variations in the manufacturing processes, the 3D printed objects might have different dimensions than the CAD models.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these geometrical properties can improve the engineering performance of a component. Moreover, AM can reduce the "cradle-to-gate" environmental footprint of component manufacturing through the avoidance of the tools, dies, and materials scrap associated with subtractive processes [7]. This allows for low-waste, sustainable design strategies.…”
Section: Introductionmentioning
confidence: 99%
“…SLM technology is used to produce high-value parts with very complex designs, which cannot be made with conventional technologies; the high cost of this process prevents its extensive use in industry, but combined parts made in AM with parts made with conventional technologies at low production costs make its use in industrial production possible, making hybrids that use AM technology only where it is really needed [19].…”
Section: Introductionmentioning
confidence: 99%